Maximized song learning of juvenile male zebra finches following BDNF expression in the HVC. Issue 9 (11th August 2013) - Dittrich, Falk; ter Maat, Andries; Jansen, Rene F.; Pieneman, Anton; Hertel, Moritz; Frankl‐Vilches, Carolina; Gahr, Manfred
Abstract: During song learning, vocal patterns are matched to an auditory memory acquired from a tutor, a process involving sensorimotor feedback. Song sensorimotor learning and song production of birds is controlled by a set of interconnected brain nuclei, the song control system. In male zebra finches, the beginning of the sensorimotor phase of song learning parallels an increase of the brain‐derived neurotrophic factor (BDNF) in just one part of the song control system, the forebrain nucleus HVC. We report here that transient BDNF‐mRNA upregulation in the HVC results in a maximized copying of song syllables. Each treated bird shows motor learning to an extent similar to that of the selected best learners among untreated zebra finches. Because this result was not found following BDNF overexpression in the target areas of HVC within the song system, HVC‐anchored mechanisms are limiting sensorimotor vocal learning. Abstract : Song sensorimotor learning and song production of birds is controlled by a set of interconnected brain nuclei, the song control system. In male zebra finches, the beginning of the sensorimotor phase of song learning parallels an increase of the brain‐derived neurotrophic factor (BDNF) in just one part of the song control system, the forebrain nucleus HVC. The transient BDNF‐mRNA upregulation in the HVC results in a maximized copying of song syllables indicating that HVC anchored mechanisms are limiting sensorimotor vocal learning.